Transformasi Digital Marketing untuk Meningkatkan Minat Beli Konsumen di Shopee - Rezki Abdillah (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The purpose of this study was to determine whether digital marketing media can influence consumer interaction with the Shopee marketplace. Online communication and sales are new things in the realm of marketing thanks to the rapid development of technology that allows individuals to make transactions through digital platforms. Currently, buying and selling transactions in the marketplace are in great demand and are popular with the public. One of the applications most often used by the public is Shopee. By using a digital marketing strategy in the Shopee marketplace, selling products without having to meet face to face with consumers becomes very easy. Business actors also try to apply efficient tactics to influence the level of consumer buying interest. In this study, the researcher applied a qualitative method that was explained descriptively by utilizing books, websites, and related journals. The quality and unique characteristics of the products being promoted